أثر المسؤولية الاجتماعية على الأداء الوظيفي دراسة حالة الفرع التجاري وفرع الوقود لمؤسسة نفطال بالوادي - مرغني مباركة; خلافي فريال; شراديد ميسون (جامعة الوادي University Of Eloued, 2025)
تهدف الدراسة إلى التعرف على أثر المسؤولية الاجتماعية على الأداء الوظيفي في الفرع التجاري وفرع الوقود لمؤسسة نفطال بالوادي وللتحقيق اهداف الدراسة تم الاعتماد على االأداة الرئسية للإستبيان لجمع البيانات وإستعنا بالمقابلة،إذ تمكنا من جمع 78 استبيان صالح لتحليل الاحصائي، حيث قمنا بتحليل هده البيانات عن طريق استخدام برنامج التحليل الاحصائي(SPSS) نسخة 25 بإضافة الى مجموعة من الأساليب الإحصائية ،لخصت الدراسة إلى نتيجة مفادها أن المسؤولية الاجتماعية سائدة بدرجة مرتفعة ولها أثر إجابي على الأداء الوظيفي، كذلك عدم وجود فروق ذات دلالة إحصائية في تصور افراد العينة حول المسؤولية الاجتماعية والأداء الوظيفي. the present study seeks to examine the influence of social responsibility on job performance within the commercial and fuel division of NAFTAL Corporation in El Oued. To fulfill the study's objectives, we relied on interviews and questionnaires as the primary data collection methods, successfully gathering 78 valid questionnaires for statistical analysis. The data were analyzed using the Statistical Package for the Social Sciences (SPSS) version 25, alongside a range of statistical techniques. The study concluded that social responsibility is prevalent to a significant extent and exerts a positive influence on job performance. Furthermore, no statistically significant differences were observed in the perceptions of the sample members regarding social responsibility and job performance
ماستر
Keywords: المسؤولية الاجتماعية; الأداء الوظيفي; Social Responsibility; Job Performance